Circulating Extracellular DNA: Cause or Consequence of Thrombosis? - Jiménez-Alcázar, Miguel; Kim, Natalie; Fuchs, Tobias A. (Seminars in Thrombosis and Hemostasis, 2017)
Thrombosis leads to ischemic organ damage in cardiovascular and thromboembolic diseases. Neutrophils promote thrombosis in vitro and in vivo by releasing neutrophil extracellular traps (NETs). NETs are composed of DNA filaments coated with histones and neutrophil enzymes such as myeloperoxidase (MPO). Circulating extracellular DNA (ceDNA) is widely used as a surrogate marker to monitor NET formation in thrombosis. This narrative review summarizes the association of ceDNA with human thrombosis. Levels of ceDNA indicate the extent and outcome of several cardiovascular and thromboembolic diseases, including myocardial infarction, stroke, and venous thromboembolism. ceDNA correlates with markers of coagulation and platelet consumption, thus supporting the hypothesis that ceDNA may be a surrogate marker of thrombus formation. In addition, ceDNA levels correlate with markers of cell injury and size of ischemic lesions, suggesting that ceDNA does not derive from NETs but is probably released from damaged organs. Few studies identified NET-specific biomarkers such as DNA–MPO complexes in the blood of patients with thrombosis. In conclusion, it remains to be established whether ceDNA in patients derives from NETs and is a cause or consequence of thrombosis.
Keywords: thrombosis; biomarker; extracellular DNA; cell-free DNA; plasma DNA; neutrophil extracellular traps